2018
DOI: 10.3847/1538-4357/aaa1e2
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved Dust, Gas, and Star Formation in the Dwarf Magellanic Irregular NGC 4449*

Abstract: We investigate the relation between gas and star formation in subgalactic regions, ∼360pc to ∼1.5kpc in size, within the nearby starburst dwarf NGC 4449, in order to separate the underlying relation from the effects of sampling at varying spatial scales. Dust and gas mass surface densities are derived by combining new observations at 1.1mm, obtained with the AzTEC instrument on the Large Millimeter Telescope, with archival infrared images in the range 8-500μm from the Spitzer Space Telescope and the Hersch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 115 publications
10
21
0
Order By: Relevance
“…AD12 (their Appendix F) found that even when the global photometry has PACS/MIPS ≈ 1, the PACS and MIPS images (with PACS convolved to the MIPS PSF) can have local surface brightnesses discrepant by factors as large as 1.5-2.0. Similar discrepancies were found when comparing PACS and MIPS imaging of M31 (Draine et al 2014) and NGC 4449 (Calzetti et al 2018). Figure 2 illustrates that even after summing over the full galaxy mask, PACS70 and MIPS70 often disagree by more than a factor 1.2, and sometimes up to a factor 1.4.…”
Section: Why Both Mips and Pacs Are Neededsupporting
confidence: 60%
“…AD12 (their Appendix F) found that even when the global photometry has PACS/MIPS ≈ 1, the PACS and MIPS images (with PACS convolved to the MIPS PSF) can have local surface brightnesses discrepant by factors as large as 1.5-2.0. Similar discrepancies were found when comparing PACS and MIPS imaging of M31 (Draine et al 2014) and NGC 4449 (Calzetti et al 2018). Figure 2 illustrates that even after summing over the full galaxy mask, PACS70 and MIPS70 often disagree by more than a factor 1.2, and sometimes up to a factor 1.4.…”
Section: Why Both Mips and Pacs Are Neededsupporting
confidence: 60%
“…The post-Planck correction factor described in Aniano et al (2020) has been applied to the value of M dust . The high value of U min , U min 12, is not uncommon in regions of strong star formation (e.g., Calzetti et al 2018). Using the formula of Draine et al (2014), the characteristic dust temperature in the Central Region of NGC 3351 is T d ∼27 K, consistent with its starburst nature, and in agreement with the temperature determination of Nersesian et al (2020).…”
Section: Dust Emission Propertiessupporting
confidence: 74%
“…The emission in each band will also be proportional to the total dust mass, M dust . and Aniano et al (2020) established that the derived dust emission parameters are not sensitive to the choice of U max , which we fix at a value of 10 5 , borrowing from the study of Calzetti et al (2018). Thus, for each given extinction curve, there are a total of four parameters for the models: q P AH , U min , γ, and M dust .…”
Section: Dust Emission Modelsmentioning
confidence: 99%
“…Evans et al 2009Evans et al , 2014Heiderman et al 2010;Gutermuth et al 2011), in starburst galaxies (e.g. Genzel et al 2010Genzel et al , 2015, in the dwarf magellanic irregular galaxy NGC 4449 (Calzetti et al 2018), and also in galactic centres (e.g. Leroy et al 2013).…”
Section: Introductionmentioning
confidence: 99%